A European Wealth Tax for a Fair and Green Recovery - Jakob Kapeller; Stuart Leitch; Rafael Wildauer (Universität Duisburg-Essen, Institut für Sozioökonomie (ifso), 2021)
The European Union faces the twin crises of Covid-19 and climate change. Confronting both crises leads to an unprecedented demand on public resources which in turn leads to the question of how to raise the required funds a) without jeopardising a weak economy recovering from the pandemic and b) without undermining broad political support for climate action. This paper investigates the potential of a European net wealth tax to raise substantial revenues while supporting the economy and the consensus on climate action. To achieve this, household survey data from the European Central Bank (covering 22 EU countries) are analysed. To address the problem of under-reporting of wealth at the top of the distribution in survey data, a Pareto distribution is fitted to the right tail of the data and used to create an amended data set which also represents these missing rich, whose wealth goes unreported. (...)
Keywords: 330